A Planet in Distress: Cross-Curricular Integrations of Visual Texts in the Mainstream Learning Context - De Jager, Nicholas; Steyn, Maretha (International Journal of Educational Development in Africa, 2023)
This article aims to explore the affordances of employing the visual mode— specifically the medium of drawing—as a multimodal pedagogy to raise awareness of deforestation and climate change in the South African mainstream school context. Conducted at several public and private schools in the Gauteng and the North West provinces, the research follows nine learners between the ages of 10 and 18, who have volunteered to participate in a three-week enrichment programme involving the multimodal reimagining of a non-curricular narrative into a series of drawings, paintings and collages. The narrative, which also serves as the primary source text during each participant’s artefactual redesign journey, is a wordless picture book that explores the concept of exponential environmental change. With this visually engaging text merely acting as a springboard for the making of new meanings in the Grade 5 to 11 Social Sciences/Geography classroom, participants are granted complete autonomy in their visual representations of how the exhaustion of our natural resources and moreover the threat of global warming may be impacting upon our daily lives on a spiritual, emotional and corporeal level. Finally, each artefact is presented as primary data to offer a tripartite focus on the latter learner experiences, the expressional properties of art, as well as the viability of the proposed pedagogy in future practice.